# Factor each of the expressions below.

A) 3 x + 3
B) 8 x + 4
C) a x + 3 a
D) (x +1) y + 4 (x + 1)
E) x + 2 + b x + 2 b
reshown Sep 3, 2018

Formula Used :  AB + AC  =  A ( B + C )

A)

3 x + 3  =  (3 X x) + (3 X 1)

=  3 (x + 1)                                                    [ Since '3' is common in both the terms ]

B)

8 x + 4  =  (8 X x) + (4 X 1)

=  (4 x 2 X x) + (4 X 1)

=  4(2x + 1)                                                   [ Since '4' is common in both the terms ]

C)

a x + 3 a   =   (a X x) + (3 X a)

=    a ( x + 3 )                                         [ Since '4' is common in both the terms ]

D)

(x +1) y + 4 (x + 1)  =   (x +1) (y + 4)                         [ Since '(x + 1)' is common in both the terms ]

E)

x + 2 + b x + 2 b   =  (x + 2) + (b X x) + (2 X b)

=  [(x + 2) X 1] + b (x+2)           [ Since 'b' is common in both the terms ]

=  (x + 2 ) (1 + b)                     [ Since '(x + 2)' is common in both the terms ]
A) 3 x + 3  =  3 (x + 1)
B) 8 x + 4  =  4(2x + 1
C) a x + 3 a   =  a ( x + 3 )
D) (x +1) y + 4 (x + 1)  =  (x +1) (y + 4)
E) x + 2 + b x + 2 b  =  (x + 2 ) (1 + b)